The Impact of the Global Economic Crisis on Financial Management Strategies - Nurul Masithoh (Universitas Muhammadiyah Palu, 2023)
Global economic crises are inevitable occurrences within the cyclical nature of the world economy, and their impacts are particularly significant for the business sector especially in terms of financial management. Economic instability, characterized by high inflation, exchange rate volatility, rising global interest rates, and declining global demand, compels companies to overhaul their financial strategies. This study aims to examine how global economic turmoil influences corporate financial management strategies, with a specific focus on the Indonesian context. Employing a qualitative descriptive approach and literature review from various national sources, the research explores adaptive strategies commonly adopted by companies. These include budget tightening, stricter cash flow control, income portfolio diversification, and the integration of financial technologies (FinTech) to enhance financial processes. The findings indicate that companies with flexible financial management structures and a high capacity for rapid macroeconomic adaptation tend to demonstrate greater resilience during crises. Furthermore, the ability to conduct risk forecasting and contingency planning also plays a critical role in maintaining financial stability. The results of this study are expected to serve as a strategic reference for financial managers in formulating robust medium- and long-term financial policies that are crisis-resistant.